2019
DOI: 10.3390/v11060502
|View full text |Cite
|
Sign up to set email alerts
|

Current In Vivo Models of Varicella-Zoster Virus Neurotropism

Abstract: Varicella-zoster virus (VZV), an exclusively human herpesvirus, causes chickenpox and establishes a latent infection in ganglia, reactivating decades later to produce zoster and associated neurological complications. An understanding of VZV neurotropism in humans has long been hampered by the lack of an adequate animal model. For example, experimental inoculation of VZV in small animals including guinea pigs and cotton rats results in the infection of ganglia but not a rash. The severe combined immune deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 148 publications
(243 reference statements)
1
23
0
1
Order By: Relevance
“…Moreover VZV infection is associated with higher risk of developing MS [102]. However appropriate animal models for the study of a role in MS are lacking, despite some attempts for the study of VZV neurotropism [103].…”
Section: Measles Rubella and Varicella Zoster (Vz) Virusesmentioning
confidence: 99%
“…Moreover VZV infection is associated with higher risk of developing MS [102]. However appropriate animal models for the study of a role in MS are lacking, despite some attempts for the study of VZV neurotropism [103].…”
Section: Measles Rubella and Varicella Zoster (Vz) Virusesmentioning
confidence: 99%
“…In the future, SVV can be obtained from leaders in the SVV field for the needed challenge studies. However, because various studies, especially Meyer et al’s report [ 3 ], have confirmed cross-reactive epitopes between SVV and VZV [ 6 8 ], it might be enough to show only the seropositivity of VZV IgG in rhesus monkeys. Although there were no comparators, such as a subcutaneously administered group and a intratracheal inoculation administered group, at the group-setting stage, our vaccination strategy produced a strong positive VZV IgG response in all vaccinated animals and suggests further testing.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the cases described in Table 1 and Table 2 gave a history of herpes zoster proceeding or concomitant with onset of symptoms of acute meningitis. After review of prior models [ 19 ], we propose a pathogenesis model ( Figure 4 ). Every child around the age of 1 year is given an initial injection of the live attenuated varicella vaccine in the thigh ( Figure 4 A).…”
Section: Pathogenesis Of Varicella Vaccine Meningitismentioning
confidence: 99%